Cognitive Level In Writing Tasks Of English Textbook At Tenth Grade Entitled “Bahasa Inggris” - Eka Saputra L S, M Yogi; Riza, Armilia; Siska, Siska (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to analyze the writing tasks in "Bahasa Inggris" textbook. The researchers examined the cognitive level of writing task and the most dominant level in this textbook based on level of Bloom's Taxonomy Revised Edition. There are 6 levels of cognitive levels, namely: Remembering, Understanding, Applying, Analyzing, Evaluating, and Creating. This research is a descriptive qualitative research  because the data collected is in the form of words. It used textbook "Bahasa Inggris" as the data source and used a checklist table in collecting and analyzing data. The researcher analyzed writing tasks in one textbook, but only focused in chapter 1 to 4. There were 13 writing tasks analyzed. The results showed that the cognitive level of tasks was only 5 levels, namely Remembering, Understanding, Applying, Analyzing, and Creating. The percentage of each level is 15.39% of 2 tasks for Remembering, 15.39% of 2 tasks for Understanding, 7.69% of 1 task for Applying, 23.07% of 3 tasks for Analyzing, and 38.46% of 5 tasks for Creating. It can be seen that there are 5 (38.46%) tasks included in Creating. This indicates that Creating has the highest percentage and has the most dominant writing task in "Bahasa Inggris" textbook.